Joint Forest Management in Raj Rishi Gram Ravan Deora: (an Inspiring Experiment of Participative Dynamics) - Chandrawat, M. P. S.; Merkap, Pramod K. (Indian Forester, 1999)
In this paper, the authors describe a nuclear model of Joint Forest Management (JFM) at Raj Rishi Gram Ravan Deora, Alwar (Rajasthan). Achievements in terms of wasteland development with planned afforestation through a peoples-based forest protection movement, encompassing cost-effective water and soil conservation, protection of wildlife through cultural heritage, integrated eco-awareness among the local inhabitats through Lok Manch and Gram Choapal as centres of continuing informal learning etc. make the model an inspiring example of self-reliant participatory dynamics. All these achievements establish the result-oriented utility of the concept of Joint Forest Management. Experimental experience and field interactions confirm that JFM is the surest way to mitigate gradually widening hiatus among the foresters, administrators, forest inhabitats, eco-social scientists, NGOs and the beneficiaries.